Social Security Organization (SOCSO) / Siti Nuraisyah Mohd Shah - Mohd. Shah, Siti Nuraisyah (Faculty of Business and Management, 2023)
During my internship at the Social Security Organization (SOCSO) of Temerloh, Pahang, I gained valuable experience in various aspects of the insurance industry. My duties included inspecting employers' premises to clear contribution arrears, holding an advocacy program with the Malaysian Motorcycle Racer Association (MMRA) to raise awareness about the importance of contributions, investigating accident cases, and distributing flyers to raise awareness for employers to register businesses and employees under SOCSO's schemes. I also investigated accident cases and provided assistance to the next of kin or accident victims. I also gained knowledge about Canva by creating posters about housewife schemes and self-employment schemes. My internship at SOCSO Temerloh allowed me to develop communication skills, update and upload data into the system, respond to phone calls, and create marketing tools. Additionally, I gained expertise in Microsoft applications such as Words, Excel, PowerPoint, and Canva. SOCSO is known for protecting employees' rights, offering low-cost insurance with high protection and perks. They also have a unique contribution system for housewives, known as the "Skim Keselamatan Sosial Suri Rumah" (SKSSR), which protects housewives in case of accidents while performing housekeeping. SOCSO is a public-private partnership in the insurance industry, offering insurance to both companies and employees. They have expanded their system to include self-employed people, housewives, and others. SOCSO has also expanded its services to include self-employed people, housewives, and other individuals. In conclusion, my internship at SOCSO Temerloh provided me with valuable experience in various aspects of the insurance industry, including the Employment Insurance Scheme (EIS) and other statutory insurance bodies. I am satisfied with my choice to work at SOCSO and the opportunities it offers for personal growth and professional development. SOCSO is a statutory authority that provides free services, but it has also expanded its system to include self-employed people, housewives, and others. The EIS deduction is designed to protect workers' rights and help them find new jobs. However, the system is vulnerable to hackers attempting to hack into it, as it requires personal data from contributors to complete necessary procedures. Lastly, employers in remote areas with limited IT skills face challenges in using the SOCSO system, making it difficult for them to make payments or write checks. This makes it difficult for them to use the system for payroll, dismissing personnel, and making payments. Overall, my internship at SOCSO has provided valuable insights and experience for my future career.